1996
DOI: 10.1002/(sici)1096-9071(199611)50:3<263::aid-jmv9>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation of common marmosets with vaccinia virus expressing Epstein-Barr virus (EBV) gp340 and challenge with EBV

Abstract: Epstein-Barr virus (EBV) is the cause of infectious mononucleosis and is associated with a variety of life-threatening diseases in humans. Therefore the development of an effective vaccine is an important objective. Many of the initial studies of vaccine efficacy analyse the ability of vaccine preparations to prevent the induction of lymphomas in cottontop tamarins by the B95-8 strain of EBV. We used a vaccinia virus recombinant expressing gp340, vMA1, tested previously in the cotton-top tamarin, to evaluate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…EBV gp350 is the most abundant EBV envelope protein, and about half of the EBV neutralizing activity in EBV seropositive human sera is against gp350 (7,161). Purified or recombinant gp350 was shown to protect cotton top tamarins from lymphoma caused by EBV infection, and similar results were reported with adenovirus or vaccinia virus expressing gp350 (69)(70)(71)(72)(73)(74)(75)(76). Phase I and II studies of a recombinant gp350 produced in Chinese hamster ovary cells showed that the recombinant gp350 induced neutralizing antibodies in humans in 70% of the subjects, and reduced the rate of infectious mononucleosis by 78% in the vaccinated subjects but did not prevent EBV infection (156,167).…”
Section: Recombinant Ebv Envelope Protein Vaccinesmentioning
confidence: 68%
“…EBV gp350 is the most abundant EBV envelope protein, and about half of the EBV neutralizing activity in EBV seropositive human sera is against gp350 (7,161). Purified or recombinant gp350 was shown to protect cotton top tamarins from lymphoma caused by EBV infection, and similar results were reported with adenovirus or vaccinia virus expressing gp350 (69)(70)(71)(72)(73)(74)(75)(76). Phase I and II studies of a recombinant gp350 produced in Chinese hamster ovary cells showed that the recombinant gp350 induced neutralizing antibodies in humans in 70% of the subjects, and reduced the rate of infectious mononucleosis by 78% in the vaccinated subjects but did not prevent EBV infection (156,167).…”
Section: Recombinant Ebv Envelope Protein Vaccinesmentioning
confidence: 68%
“…Viral vectors have the advantage of possessing intrinsic immune-stimulating capabilities and thus do not require administration with adjuvants; in addition, they can be combined with VLP platforms to produce VLPs in vivo ( 142 144 ). The 6 pre-clinical EBV vaccine studies using viral vectors tested measles virus ( 55 ), adenovirus ( 64 ), and vaccinia virus vectors ( 57 , 61 , 70 , 75 ) ( Table 3 ); the latter was also tested in one of the 4 EBV vaccine clinical trials [( 83 ), Table 4 ]. In these studies, the vectors were engineered to express single antigens, but viral vectors with the necessary genetic insert capacity can be engineered to express multiple antigens.…”
Section: Discussionmentioning
confidence: 99%
“…As different approaches to gp350-based EBV vaccination, vaccinia virus and adenovirus were used as viral vectors to express gp350. The WR strain of vaccinia virus expressing gp350 (VV-gp350) induced humoral immune responses in rabbits, cottontop tamarins, and common marmosets 68 , 69 , 73 . It is remarkable that although no anti-gp350 antibodies and low levels of neutralizing antibodies were detected in cottontop tamarins inoculated with VV-gp350, three out of four animals were still free of lymphoma after an EBV challenge with a dose of 10 5.3 lymphocytes-transforming doses that cause tumors in 100% of unvaccinated tamarins 73 .…”
Section: Where Are We Now?mentioning
confidence: 99%
“…four times at a 4-week interval B95-8 3/5 were free of lymphoma after 100% tumorigenesis dose challenge 60 1996 Common marmosets Recombinant vaccinia virus expressing gp350 i.d. twice at a 5-week interval M81 Replication of the challenge virus was decreased 69 1998 Common marmosets recombinant gp350 with BPV + alum i.m. three times at a 4-week interval M81 Replication of the challenge virus was decreased 55 None there is no challenge experiment, ADCC antibody-dependent cell-mediated cytotoxicity.…”
Section: Where Are We Now?mentioning
confidence: 99%